COAL GASIFICATION STUDY OF INDONESIAN COAL USING THERMOGRAVIMETRIC ANALYSIS (TGA): A CASE STUDY OF COAL FROM MEULABOH AND BARITO BASINS - Al Hamda, Aisyah
Coal is one of the abundant natural resources in Indonesia and has great potential for sustaining the energy sector. One environmentally friendly utilization of coal is coal gasification. An important factor in the gasification process is gasification reactivity. The characteristics of coal and the composition of coal macerals in Indonesia vary according to their depositional environment, so they need to be studied to determine their role in coal gasification reactivity. This study used two samples from the Meulaboh Basin (BB-01 and BB02) and one sample from the Barito Basin (BB-03). Gasification reactivity testing was conducted using thermogravimetric analysis with three treatment segments: heating the sample from 50°C to 900°C with a temperature increase rate of 10°C/minute using an argon (Ar) atmosphere, conditioning the sample for 10 minutes to obtain an isothermal state, and finally changing the atmosphere to 100% carbon dioxide (CO2). Coal characteristics were interpreted from the results of proximate analysis, ultimate analysis, and calorific value analysis, while coal maceral composition was interpreted from the results of coal petrographic analysis. Samples BB-01 and BB-02 were classified as sub-bituminous C ranks, while sample BB-03 was classified as high-volatile A bituminous ranks. In the gasification process, sample BB-01 showed a greater reduction in mass, indicating higher reactivity compared to samples BB-02 and BB-03. The rate of mass reduction in sample BB-01 was higher than that of sample BB-02 at the same rank because sample BB-02 had a significantly higher mineral content, which reduced the amount of organic matter available for reaction. Gasification reactivity is influenced by various factors such as rank, maceral composition, porosity, and mineral content, but in this study, there was a dominant factor that played a significant role in influencing gasification reactivity, which was the coal rank